Effects of silica nanoparticles and calcium chelate on the morphological, physiological and biochemical characteristics of gerbera (Gerbera jamesonii L.) under hydroponic condition. (21st April 2021) - Tofighi Alikhani, Tahereh; Tabatabaei, Seyed Jalal; Mohammadi Torkashvand, Ali; Khalighi, Ahmad; Talei, Daryush
Abstract: A factorial experiment, in the form of completely randomized design with two factors, was conducted in four replicates to investigate the effects of silica nanoparticles (nanoparticle-SiO2 ) and calcium chelate (Ca-chelate) on gerbera ( Gerbera jamesonii L.). The first factor was nanoparticle-SiO2 concentration in nutrient solution (at four levels of 0, 20, 40 and 80 mg L −1 ) and the second factor was Ca-chelate concentration in nutrient solution (at four levels of 0, 60, 120 and 240 mg L −1 ). Number of leaves, number of flowers, number of flower buds and aborted flower buds, time of flowering, flower vase life, flower color, percentages of ash and lignin in stem, petal protein, as well as the amounts of silica and calcium in stem, leaf and root were measured. Compared to control, the treatment of 80 mg L −1 of nanoparticle-SiO2 with 60 mg L −1 of Ca-chelate increased the number of flowers by 182%. Moreover, applying 60 mg L −1 of Ca-chelate and 20 mg L −1 of nanoparticle-SiO2 led to flowers with 1.5 times higher longevity and 27% increase in flowering rate. The highest flower bud numbers and the lowest bud abortion were obtained in the treatment with 80 mg L −1 of nanoparticle-SiO2 and 60 mg L −1 of Ca-chelate. The highest concentration of calcium in stem, leaf and root as well as the highest amount of protein, pigment intensity and degree of transparency were observed in the treatment with 240 mg L −1 of Ca-chelate and 80 mg L −1 of nanoparticle-SiO2 .